Palladium-supported carbon nitride and its application in photocatalytic reduction of elagolide intermediates
By using palladium-supported carbon nitride as a photocatalyst, 2-fluoro-6-trifluoromethylbenzaldehyde oxime is reduced to 2-fluoro-6-trifluoromethylbenzylamine under mild conditions, solving the problems of harsh reaction conditions and the use of toxic substances in the prior art, and achieving an efficient and green synthesis process.
Patent Information
- Application Number
- CN202310588713.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-05-24
AI Technical Summary
In the prior art, the reduction process of the key intermediate 2-fluoro-6-trifluoromethylbenzaldehyde oxime for synthesis of oxalagoli drugs requires high-pressure hydrogen and toxic boronane, and the reaction conditions are harsh, making it difficult to achieve efficient and green synthesis.
Palladium-supported carbon nitride was used as the photocatalyst to reduce 2-fluoro-6-trifluoromethylbenzaldehyde oxime to 2-fluoro-6-trifluoromethylbenzylamine under mild photocatalytic conditions. The method includes synthesizing the carbon nitride precursor by thermal polymerization, and then synthesizing high crystallinity carbon nitride through molten salt method, and adding palladium salt to the light reaction to achieve the synthesis of palladium-supported carbon nitride.
It has achieved efficient catalyzing of the reduction of 2-fluoro-6-trifluoromethylbenzaldehyde oxime under mild conditions to produce 2-fluoro-6-trifluoromethylbenzylamine, and the reaction conditions are safe and environmentally friendly, and meet the requirements of large-scale promotion.
Smart Images

Figure CN116603560B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic materials, and specifically relates to a palladium-loaded carbon nitride and a preparation method thereof, and application thereof in photocatalytic reduction of 2-fluoro-6-trifluoromethylbenzaldehyde oxime, a key intermediate of elagolix, to 2-fluoro-6-trifluoromethylbenzylamine. Background Art
[0002] The U.S. FDA approved ORILISSA through priority review TM Elagolix is used to treat women with moderate to severe endometriosis pain. It is the only oral gonadotropin-releasing hormone (GnRH) antagonist with the following chemical formula:
[0003] .
[0004] 2-Fluoro-6-trifluoromethylbenzylamine is a key intermediate in the synthesis of the drug Elagolix. The conventional synthesis method is to reduce 2-fluoro-6-trifluoromethylbenzonitrile with borane (patent WO2005007165A). Due to the high toxicity of borane and the fact that the reduction of benzonitrile usually requires harsh reaction conditions such as high-pressure hydrogen, lithium aluminum hydride, and sodium borohydride, it is particularly important to develop a method for efficiently and greenly synthesizing 2-fluoro-6-trifluoromethylbenzylamine under mild reaction conditions.
[0005] Graphitic carbon nitride (g-CN) polymer is the most stable allotrope of binary carbon nitride materials under ambient conditions. Due to its unique physicochemical properties, it was successfully used as a metal-free visible light photocatalyst in 2009 (Nat. Mater. 2009, 8, 76−80.). It has also been actively studied in the process of converting solar energy into chemical energy, such as water hydrogen production, CO2 conversion (Energy Environ. Sci. 2015, 8, 3092-3108.) and organic selective synthesis (Angew. Chem., Int. Ed. 2015, 54, 12868-12884). Summary of the invention
[0006] The object of the present invention is to provide a palladium-loaded carbon nitride and a preparation method thereof. The obtained palladium-loaded carbon nitride is used as a photocatalyst, 2-fluoro-6-trifluoromethylbenzaldehyde oxime, which is easier to reduce than 2-fluoro-6-trifluoromethylbenzonitrile, can be used as a reaction substrate, and the synthesis of 2-fluoro-6-trifluoromethylbenzylamine can be achieved under milder photocatalytic conditions.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] A palladium-supported carbon nitride, which is prepared by first subjecting a carbon nitride precursor to a thermal polymerization reaction to synthesize bulk carbon nitride (PCN); then adding an inorganic salt to synthesize high-crystallinity carbon nitride (CCN) by a molten salt method; and then using a palladium salt as a metal source to synthesize the palladium-supported carbon nitride (Pd-CCN) by a photoreduction method; the method specifically comprises the following steps:
[0009] 1) calcining the carbon nitride precursor in a muffle furnace and grinding it to obtain bulk carbon nitride;
[0010] 2) The prepared bulk carbon nitride and inorganic salt are fully ground and placed in a tube furnace. After calcination in a nitrogen atmosphere, the product is washed with deionized water and methanol, and then dried to obtain high-crystallinity carbon nitride;
[0011] 3) adding alcohol and deionized water to the prepared high-crystallinity carbon nitride, and then adding an acid solution containing a palladium salt dropwise, stirring and then irradiating with light for a certain period of time, washing the obtained product with deionized water and ethanol and then vacuum drying to obtain the palladium-loaded carbon nitride.
[0012] Furthermore, in step 1), the carbon nitride precursor is selected from one or more of cyanamide, dicyandiamide, thiourea, urea, and melamine; the heating rate of the calcination is 5-20 °C·min -1 , temperature is 400-600 ℃, time is 120~360min.
[0013] Furthermore, the mass ratio of bulk carbon nitride to inorganic salt used in step 2) is (0.1-2):(1-30); the inorganic salt is selected from one or more of NaCl, KCl, LiCl, MgCl2, LiBr, KBr, NaBr, and MgBr2; the heating rate of the calcination is 3-15 °C·min -1 , temperature is 400-600 ℃, time is 120-360min; the unit structure of the obtained high crystallinity carbon nitride is:
[0014] .
[0015] Furthermore, the mass ratio of high-crystallinity carbon nitride to palladium salt used in step 3) is (10-50):(1-5), and the palladium salt is one or more of palladium dichloride, palladium dibromide, and palladium acetate; the volume ratio of alcohol and deionized water used is (1-25):(10-50), and the alcohol is one or more of methanol, ethanol, isopropanol, and ethylene glycol; the acid solution is an aqueous solution of one or more of hydrochloric acid, sulfuric acid, phosphoric acid, and nitric acid, and its concentration is 0.1-10 M; the stirring time is 10-30 min; the light source used for illumination is an artificial light source that can achieve the effect of sunlight, with a power of 10-100 watts and a wavelength of 250-600 nm; the light reaction time is 120-360 min; the volume ratio of deionized water and ethanol used for washing is (1-2):(0.5-1), and the vacuum drying temperature is 60-120 ° C and the time is 5-24 h.
[0016] The palladium-supported carbon nitride exhibits good photocatalytic activity in reducing the key intermediate of Elagolix, 2-fluoro-6-trifluoromethylbenzaldehyde oxime, to 2-fluoro-6-trifluoromethylbenzylamine under visible light irradiation, and can thus be used to efficiently catalyze the reduction of 2-fluoro-6-trifluoromethylbenzaldehyde oxime to 2-fluoro-6-trifluoromethylbenzylamine under visible light conditions, and the reaction formula is as follows:
[0017] ;
[0018] Specifically, 2-fluoro-6-trifluoromethylbenzaldehyde oxime is used as a raw material, an organic acid is used as a hydrogen source, and an inorganic acid is used as a reaction solvent. In an inert gas, the palladium-loaded carbon nitride is used as a photocatalyst and irradiated under a fixed light source for a certain period of time to generate 2-fluoro-6-trifluoromethylbenzylamine.
[0019] Furthermore, the mass ratio of the key intermediate of elagolix, the hydrogen source and the photocatalyst used is 21:5:40, the organic acid is one or more of methanol, ethanol, formic acid, acetic acid, and oxalic acid; the inorganic acid is one or more of hydrochloric acid, sulfuric acid, and phosphoric acid; the light source used is a 100-watt xenon lamp, an LED lamp or sunlight; and the irradiation time is 1 hour.
[0020] The significant advantages of the present invention are:
[0021] (1) The palladium-loaded carbon nitride prepared by the present invention has good visible light response and can effectively catalyze the reduction of 2-fluoro-6-trifluoromethylbenzaldehyde oxime to 2-fluoro-6-trifluoromethylbenzylamine (the complete conversion of 2-fluoro-6-trifluoromethylbenzaldehyde oxime can be achieved in 60 minutes under nitrogen conditions), and is a highly efficient photocatalyst.
[0022] (2) The palladium-loaded carbon nitride prepared in the present invention has good chemical stability.
[0023] (3) The entire production process of the present invention is simple, easy to control, has low energy consumption and low cost, meets actual production needs, and is conducive to large-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a comparison chart of infrared spectra of PCN, CCN and Pd-CCN synthesized in Example 1.
[0025] Figure 2 2 are the XRD patterns of PCN, CCN and Pd-CCN synthesized in Example 1.
[0026] Figure 3 This is a component analysis diagram of the product obtained by photocatalytic reduction of 2-fluoro-6-trifluoromethylbenzaldehyde oxime using Pd-CCN in Example 2.
[0027] Figure 4 This is a component analysis diagram of the product obtained by photocatalytic reduction of 2-fluoro-6-trifluoromethylbenzaldehyde oxime using Pd-PCN in Example 2.
[0028] Figure 5 This is a component analysis diagram of the product obtained by photocatalytic reduction of 2-fluoro-6-trifluoromethylbenzaldehyde oxime using CCN+PdCl2 in Example 2.
[0029] Figure 6 This is a comparison chart of the activity of different catalyst samples in Example 2 for photocatalytic reduction of 2-fluoro-6-trifluoromethylbenzaldehyde oxime. DETAILED DESCRIPTION
[0030] A palladium-supported carbon nitride, the preparation method of which comprises the following steps:
[0031] 1) Synthesis of bulk carbon nitride: The carbon nitride precursor is calcined in a muffle furnace and then ground to obtain bulk carbon nitride;
[0032] 2) Synthesis of high-crystalline carbon nitride: The prepared bulk carbon nitride and inorganic salt are fully ground and placed in a tube furnace. After calcination in a nitrogen atmosphere, the product is washed with deionized water and methanol, and then dried to obtain high-crystalline carbon nitride;
[0033] 3) Synthesis of palladium-loaded carbon nitride: alcohol and deionized water are added to the prepared high-crystallinity carbon nitride, and then an acid solution containing a palladium salt is added dropwise. After stirring, the mixture is exposed to light for a certain period of time. The product is washed with deionized water and ethanol and then vacuum dried to obtain the palladium-loaded carbon nitride.
[0034] Wherein, in step 1), the carbon nitride precursor is selected from one or more of cyanamide, dicyandiamide, thiourea, urea, and melamine; the heating rate of the calcination is 5-20 °C·min-1 (Preferably 10~20 ℃·min -1 ), the temperature is 400-600 ℃ (preferably 500-550 ℃), and the time is 120~360 min (preferably 120-240 ℃).
[0035] Step 2) The mass ratio of bulk carbon nitride to inorganic salt is (0.1-2):(1-30) (preferably (0.1-1):(5-10)); the inorganic salt is selected from one or more of NaCl, KCl, LiCl, MgCl2, LiBr, KBr, NaBr, and MgBr2; the heating rate of the calcination is 3-15 °C·min -1 (Preferably 5~15 ℃·min -1 ), the temperature is 400-600 ℃ (preferably 500-550 ℃), and the time is 120-360 min (preferably 120-240 min).
[0036] The mass ratio of the high-crystallinity carbon nitride to the palladium salt used in step 3) is (10-50):(1-5) (preferably (30-40):(1-3)), and the palladium salt is one or more of palladium dichloride, palladium dibromide, and palladium acetate; the volume ratio of the alcohol and deionized water used is (1-25):(10-50) (preferably (1-10):(2-4)), and the alcohol is one or more of methanol, ethanol, isopropanol, and ethylene glycol; the acid solution is an aqueous solution of one or more of hydrochloric acid, sulfuric acid, phosphoric acid, and nitric acid, and its concentration is 0.1-10M (preferably 1-10M); the stirring time is 10-30min (preferably 10-20min); the light source used for illumination is an artificial light source that can achieve the effect of sunlight, and its power is 10-100 watts (preferably 50-100 watts) and the wavelength is 250-600 nm (preferably 350-500 nm); the time used for the light irradiation reaction is 120-360 min (preferably 120-240 min); the volume ratio of deionized water and ethanol used for washing is (1-2):(0.5-1), the temperature of the vacuum drying is 60-120 ° C (preferably 60-100 ° C), and the time is 5-24 h (preferably 10-24 h).
[0037] The obtained palladium-loaded carbon nitride can be used for photocatalytic reduction of a key intermediate of elagolix, which specifically uses the key intermediate of elagolix 2-fluoro-6-trifluoromethylbenzaldehyde oxime as a raw material, an organic acid as a hydrogen source, and an inorganic acid as a reaction solvent. In an inert gas, the palladium-loaded carbon nitride is used as a photocatalyst and irradiated under a fixed light source for a certain period of time to generate 2-fluoro-6-trifluoromethylbenzylamine.
[0038] The mass ratio of the key intermediate of elagolix, the hydrogen source and the photocatalyst used is 21:5:40; the organic acid is one or more of methanol, ethanol, formic acid, acetic acid and oxalic acid; the inorganic acid is one or more of hydrochloric acid, sulfuric acid and phosphoric acid; the light source used is a 100-watt xenon lamp, an LED lamp or sunlight; and the irradiation time is 1 hour.
[0039] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0040] Example 1
[0041] Cyanamide (10 g) was placed in a porcelain crucible and then transferred to a muffle furnace at 10 °C min -1 The temperature was raised to 500 °C at a rate of 1.5 °C and calcined for 3 hours. Bulk carbon nitride (PCN) was obtained by grinding. Then, 500 mg of bulk carbon nitride was fully ground with 4 g of NaCl and 2 g of LiCl, transferred to a porcelain crucible, placed in a tube furnace, and heated at 10 °C min in an argon atmosphere. -1 The temperature was raised to 500 °C at a rate of 1.50 °C and calcined for 4 h. The product was washed several times with 1 L of deionized water and 0.5 L of methanol to remove excess salt and then dried in an oven at 60 °C for 15 h to obtain high crystalline carbon nitride (CCN).
[0042] Take 400 mg of high-crystalline carbon nitride, add 1 mL of methanol and 20 mL of deionized water, then add 5 mL of 5M sulfuric acid solution containing 20 mg of palladium acetate dropwise, stir for 10 minutes, irradiate with a 100 W xenon lamp for 4 hours, then wash with 1 L of deionized water and 0.5 L of ethanol, and vacuum dry at 60 °C for 12 hours to obtain palladium-loaded carbon nitride (Pd-CCN).
[0043] Figure 1 The infrared spectra of the synthesized PCN, CCN and Pd-CCN are compared. As can be seen from the figure, the spectra of PCN and CCN are similar, with a peak of 3000 to 3600 cm -1 There is a broad absorption peak at 1700 to 900 cm -1 The absorption peak between the two is attributed to the vibration of the heptazine ring. The structure of CCN did not change significantly after palladium loading, indicating that the structure of the catalyst remained stable before and after loading.
[0044] Figure 2The XRD patterns of the synthesized PCN, CCN and Pd-CCN are shown in Figure 1. As can be seen from the figure, the half-peak width at 2θ=28 of CCN prepared by ion thermal treatment is smaller than that of PCN, indicating that its crystallinity is improved. The 111 crystal plane of palladium appears in the XRD after palladium loading, proving the successful loading of palladium.
[0045] Example 2
[0046] Take 5 mg of different catalyst samples (Pd-PCN, Pd-CCN and CCN+PdCl2 (mass ratio 1:1)), place them in a 10 ml glass reactor, add 2 mL of 1 M sulfuric acid solution, add a stirrer and 40 mg of oxalic acid, 21 mg of 2-fluoro-6-trifluoromethylbenzaldehyde oxime, fill with nitrogen, react at 45 ° C under LED lighting conditions for 60 minutes, and analyze the reaction products using high performance liquid chromatography.
[0047] Figure 3 The composition analysis diagram of the products obtained by photocatalytic reduction using Pd-CCN. It can be seen from the figure that the main product of 2-fluoro-6-trifluoromethylbenzaldehyde oxime catalyzed by Pd-CCN is 2-fluoro-6-trifluoromethylbenzylamine, with a conversion rate of 99% and a selectivity of 95%.
[0048] Figure 4 The composition analysis diagram of the product obtained by photocatalytic reduction using Pd-PCN. It can be seen from the figure that the conversion rate of 2-fluoro-6-trifluoromethylbenzaldehyde oxime catalyzed by Pd-PCN is 27% and the selectivity is 40%.
[0049] Figure 5 The component analysis diagram of the product obtained by photocatalytic reduction using CCN+PdCl2. It can be seen from the figure that the conversion rate of 2-fluoro-6-trifluoromethylbenzaldehyde oxime catalyzed by CCN+PdCl2 is 99%, and the selectivity is 27%.
[0050] Figure 6 The activity comparison chart of different catalyst samples for photocatalytic reduction of 2-fluoro-6-trifluoromethylbenzaldehyde oxime. As can be seen from the figure, Pd-CCN has the highest yield of 95%, while the yields of the other catalysts are very low.
[0051] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. Application of palladium-supported carbon nitride in photocatalytic reduction reaction of key intermediates of elagolix, characterized in that: The method uses 2-fluoro-6-trifluoromethylbenzaldehyde oxime, a key intermediate of elagolix, as a raw material, an organic acid as a hydrogen source, an inorganic acid as a reaction solvent, and uses the palladium-supported carbon nitride as a photocatalyst in an inert gas and irradiates under a fixed light source for a certain period of time to generate 2-fluoro-6-trifluoromethylbenzylamine.
2. The use according to claim 1, characterized in that: The preparation of the palladium-supported carbon nitride comprises the following steps: 1) synthesizing bulk carbon nitride by thermal polymerization of a carbon nitride precursor; 2) Add inorganic salts and synthesize high-crystalline carbon nitride by molten salt method; 3) Using palladium salt as a metal source, a photoreduction method is adopted to synthesize the palladium-supported carbon nitride.
3. The use according to claim 2, characterized in that: Step 1) specifically involves calcining the carbon nitride precursor in a muffle furnace and then grinding it to obtain bulk carbon nitride.
4. The use according to claim 3, characterized in that: The carbon nitride precursor is selected from one or more of cyanamide, dicyandiamide, urea, and melamine; the heating rate of the calcination is 5-20 °C·min -1 , temperature is 400-600 ℃, time is 120~360 min.
5. The use according to claim 2, characterized in that: Step 2) specifically comprises grinding the prepared bulk carbon nitride and inorganic salt thoroughly and placing them in a tubular furnace. After calcining them in a nitrogen atmosphere, the product is washed with deionized water and methanol and then dried to obtain high-crystallinity carbon nitride.
6. The use according to claim 5, characterized in that: The mass ratio of bulk carbon nitride to inorganic salt is (0.1-2):(1-30); the inorganic salt is selected from one or more of NaCl, KCl, LiCl, MgCl2, LiBr, KBr, NaBr, and MgBr2; the heating rate of calcination is 3-15 °C·min -1 , temperature is 400-600 ℃, time is 120-360 min; the unit structure of the obtained high crystallinity carbon nitride is: 。 7. The use according to claim 2, characterized in that: Step 3) specifically adds alcohol and deionized water to the prepared high-crystallinity carbon nitride, then drops the acid solution containing palladium salt, stirs and then irradiates the reaction for a certain period of time, washes the obtained product with deionized water and ethanol and then vacuum dries to obtain the palladium-loaded carbon nitride.
8. The use according to claim 7, characterized in that: The mass ratio of the high-crystallinity carbon nitride to the palladium salt is (10-50):(1-5), and the palladium salt is one or more of palladium dichloride, palladium dibromide, and palladium acetate; the volume ratio of the alcohol to deionized water is (1-25):(10-50), and the alcohol is one or more of methanol, ethanol, isopropanol, and ethylene glycol; the acid solution is an aqueous solution of one or more of hydrochloric acid, sulfuric acid, phosphoric acid, and nitric acid, and its concentration is 0.1-10 M; the light source used for illumination is an artificial light source that can achieve the effect of sunlight, and its power is 10-100 watts and the wavelength is 250-600 nm; the time used for the illumination reaction is 120-360 min.
9. The use according to claim 1, characterized in that: The mass ratio of the key intermediate of elagolix, the organic acid and the photocatalyst used is 21:5:40, the organic acid is one or more of formic acid, acetic acid and oxalic acid; the inorganic acid is one or more of hydrochloric acid, sulfuric acid and phosphoric acid; the light source used is a 100-watt xenon lamp, an LED lamp or sunlight; and the irradiation time is 1 hour.
Citation Information
Patent Citations
Pyrimidine-2, 4-dione derivatives as gonadotropin-releasing hormone receptor antagonists
WO2005007165A1
Method for preparing elagolix intermediate
CN110669014A
Monatomic palladium-loaded carbon nitride catalyst and preparation and application thereof in NO removal
CN111203260A